Comparative Genomics of Microbacterium Species to Reveal Diversity, Potential for Secondary Metabolites and Heavy Metal Resistance - Corretto, Erika; Antonielli, Livio; Sessitsch, Angela; Höfer, Christoph; Puschenreiter, Markus; Widhalm, Siegrid; Swarnalakshmi, Karivaradharajan; Brader, Günter (Frontiers in Microbiology, 2020)
Microbacterium species have been isolated from a wide range of hosts and environments, including heavy metal-contaminated sites. Here, we present a comprehensive analysis on the phylogenetic distribution and the genetic potential of 70 Microbacterium belonging to 20 different species isolated from heavy metal-contaminated and non-contaminated sites with particular attention to secondary metabolites gene clusters. The analyzed Microbacterium species are divided in three main functional clades. They share a small core genome (331 gene families covering basic functions) pointing to high genetic diversity. The most common secondary metabolite gene clusters encode pathways for the production of terpenoids, type III polyketide synthases and non-ribosomal peptide synthetases, potentially responsible of the synthesis of siderophore-like compounds. In vitro tests showed that many Microbacterium strains produce siderophores, ACC deaminase, auxins (IAA) and are able to solubilize phosphate. Microbacterium isolates from heavy metal contaminated sites are on average more resistant to heavy metals and harbor more genes related to metal homeostasis (e.g. metalloregulators). On the other hand, the ability to increase the metal mobility in a contaminated soil through the secretion of specific molecules seems to be widespread among all. Despite the widespread capacity of strains to mobilize several metals, plants inoculated with selected Microbacterium isolates showed only slightly increased iron concentrations, whereas concentrations of zinc, cadmium and lead were decreased.